Kajian Pengelolaan Biokonversi Sampah Organik melalui Budidaya Maggot Black Soldier Fly (Studi Kasus: PKPS Medan) - Restu Auliani; Bella Elsaday; Desy Ari Apsari; Helfi Nolia (Jurnal Serambi Engineering, 2021)
The cultivation of maggot Black Soldier Fly (BSF) is a bioconversion technology of organic matter that can be one solution to the problem of organic waste. This study aims to examine aspects of organic waste management through BSF Medan maggot cultivation, including operational technical, financing, institutional, regulatory and community and government participation aspects. This research is a descriptive observational study with an exploratory study approach using the interview method. Descriptive and quantitative data processing and analysis. Based on operational technical aspects, maggot cultivation has succeeded in converting organic waste into a source of animal feed protein and reducing the amount of organic waste. The amount of organic waste that is managed is 90kg/day with an effectiveness of 0.013% the total domestic waste in Medan. The financing and institutional aspects of waste management are managed in an organized manner through a cooperative body, namely the Primary Waste Management Cooperative (PKPS) Medan. The regulatory aspect that is used as reference is Medan Mayor Regulation No. 26 of 2019. Aspects of community participation directly from members of the cooperative and the Laucih wholesale market trader in Medan City. This bioconversion technology is able to overcome the problem of waste in an effort to reduce organic waste.